Comparative Study on the Sensitivity Pattern of Microorganisms - D, Vidhya; S, Sriram; Devi A.S, Manjula; B, Rajalingam; S, Shivashankar; B, Chitra; R, Rajeswari (Indian Journal of Pharmacy Practice)
Antimicrobial resistance is an issue of great significance for public health at global level. The purpose of the study is to determine the susceptibility patterns of microorganisms to antibiotics and the prevalence of antibiotic resistance among common pathogens in a tertiary care hospital. The study was conducted in a 500- bedded multi- specialty hospital in South India (for a period of six months from May 2009 to October 2009 in four different phases). A total of 4321 records were analyzed during the retrospective study (May 2006 to April 2009) which revealed that the major organisms isolated were E.coli (33.3%), Klebsiella (21.4%), S.pneumoniae (16%), S. aureus (10.7%), Pseudomonas (8.9%). The sensitivity pattern showed that E.coli, Klebsiella, S.pneumoniae, and Pseudomonas were highly sensitive to Imipenem and Piperacillin/ Tazobactam. S. aureus was sensitive to Linezolid (80%). In the prospective study (May 2009 to October 2009) a total of 956 records were screened which showed that the major organisms isolated were E.coli (37.7%), Klebsiella (24.6%), S.pneumoniae (12%), S. aureus (9.6%), Pseudomonas (7.8%). The sensitivity pattern studies revealed that E.coli was highly sensitive to Piperacillin/ Tazobactam (92.2%), Klebsiella to Cephazolin/ Sulbactam (91.5%), S.pneumoniae to Imipenem (91.3%), and Pseudomonas to Sparfloxacin (90.7%) and S. aureus to Linezolid (91.3%). On comparing the retrospective and prospective data it was seen that S.pneumoniae had developed resistance to Carbenicillin, Klebsiella to Ofloxacin, Citrobacter to Netilmicin, E.coli to Amikacin and S.aureus to Methicillin.
Keywords: Antibiotics; resistance; retrospective; sensitivity pattern